Occurrence of Lymphedema in Wild-Caught Anurans: Lymphedema in frogs - MCCALLUM, MALCOLM (Journal of North American Herpetology, 2024)
Lymphedema is a condition in which the lymph hearts fail to pump fluid from the lymph sacs of anurans and other amphibians. This causes the sacs to fill with fluid and provide the frog with balloon-like swellings or over-all appearance. The condition has previously been connected with various diseases including tadpole edema virus and chytrids. I observed lymphedema in six anuran species (Acris blanchadi*, Anaxyrus fowleri*, Hyla squirrela*, Pseudacris streckeri illinoensis*, Rana sylvatica, Rana sphenocephala* [species with * are species records for lymphedema]).